From hormones to neurodegeneration: how FSH drives Alzheimer’s disease - Xue, Yafei; Zuo, Shuqi; Wang, Fei; Qi, Xiaoyi (Frontiers in Aging Neuroscience, 2025)
The role and function of follicle-stimulating hormone in the gonads have been extremely studied. However, recent research has begun to explore the relationship between elevated follicle-stimulating hormone levels and the prevalence of extragonadal disorders, particularly in perimenopausal and postmenopausal women. These disorders include endometrial cancer, osteoporosis, obesity, and atherosclerosis. This review provides new insights into the relationship between follicle-stimulating hormone and the development of age-related diseases, with a focus on Alzheimer’s disease. Follicle-stimulating hormone does not act alone in promoting Alzheimer’s disease but often works in conjunction with inflammation, lipid accumulation, and vascular alterations. Furthermore, follicle-stimulating hormone synergizes with obesity, gut microbiota, autophagy, and aging, creating conditions that facilitate the onset and progression of Alzheimer’s disease. This review also summarizes the therapeutic potential of FSH-blocking antibodies in treating these diseases.